Prolonged use and conditionality failure: Investigating IMF responsibility - Silvia Marchesi; Laura Sabani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Since the 1970s, prolonged use of resources by the IMF has consistently expanded, among both low- and middle-income countries. Overall, this phenomenon suggests a lack of effectiveness of Fund supported programmes. In the literature conditional lending failure has been explained by looking both at the characteristics of the borrowing countries (demand-side factors) and at the possible influence of IMF specific interests (supply-side factors). Among the latter it has been suggested that noncompliance with conditionality might be attributed to the lack of credibility of the IMF threat of interrupting financial assistance in case of policy slippages. In this paper we critically review this literature and we propose a novel explanation, according to which it is the repeated nature of the IMF involvement, together with the fact that the Fund acts simultaneously as a lender and as a monitor (and as an advisor) of economic reforms, that weakens the credibility of the IMF threat. Specifically, we argue that the IMF desire to preserve its reputation as a good monitor/advisor may distort its lending decisions towards some laxity, which may be exacerbated by the length of the relationship between a country and the Fund. Therefore, we claim that prolonged use of IMF resources is not only a consequence of a lack of effectiveness of conditional lending but it might itself be a determinant of conditionality failure.
Keywords: D82; E61; F34; N2; 330; IMF conditionality; incomplete information; reputation; Anpassungsprogramm des IWF; Glaubwürdigkeit; Unvollkommene Information